(untitled) (Papeles, 2017)
This text presents a critical review of emotional mathematics while addressing the role of emotions in the reconfiguration of mathematics didactics in relation to reasonableness. For a long time rationality has been imposed on reasonableness, so that mathematics is seen as a hard area that causes displeasure and suffering to adolescents and young people. However, in the last few years a number of researches have emerged to link the cognitive with the affective and to think that an emotional education, parallel to mathematical education, contributes to raise not only the level of knowledge but also the quality of life of those who study.